Combining Static and Dynamic Recidivism Risk Information Into the Five-Level Risk and Needs System: A New Zealand Example - Coulter, Darcy J. (Criminal justice and behavior, 2022)
Communicating recidivism risk is individualized to each assessment. Labels (e.g., high, low) have no standardized meaning. In 2017, the Council of State Governments Justice Center (CSGJC) proposed a framework for standardized communication, but balancing the framework’s underlying principles of effective risk communication (and merging static and dynamic information) adds complexity. In this study, we incorporated dynamic risk scores that case managers rated among a routine sample of adults on parole in New Zealand (N = 440) with static risk scores into the Five-Level Risk and Needs System. Compared with static risk only, merging tools (a) enhanced concordance with the recidivism rates proposed by CSGJC for average and lower-risk individuals, (b) diminished concordance for higher-risk individuals, yet (c) improved conceptual alignment with the criminogenic needs domain of the system. This example highlights the importance of attending to the underlying principles of effective risk communication that motivated the development of the system.